MANAJEMEN NILAI-NILAI KOMUNITAS: UPAYA PENGUATAN KOMITMEN KERJA GURU DI SEKOLAH PEDESAAN - Nur Putri Dewi; Akmal Mundiri (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
Teachers' work commitment in rural areas is a social reality that cannot be understood solely from the perspective of individual morality or economic necessity. In addition to professional demands and ethical responsibilities, this commitment is also influenced by the social context surrounding teachers' lives. The values of togetherness, belonging, solidarity, and close social relationships within rural communities shape the interaction patterns and work ethic of educators. This study aims to deeply understand how community values in rural schools play a role in enhancing and maintaining teachers' work commitment. The study used a qualitative approach with a case study method, conducted at MI Nurul Iman, Sindetlami Village. This approach was chosen to explore the phenomenon comprehensively through various relevant data sources. Data collection techniques included direct observation, in-depth interviews, and documentation. The results indicate that religious values and character building are the main foundations for strengthening teachers' work commitment. Religious values not only shape character but also foster a sense of moral and spiritual responsibility in carrying out professional duties. Thus, a school culture based on community values in rural areas has been shown to play a significant role in fostering and sustaining teacher dedication.